The seventh international RASopathies symposium: Pathways to a cure—expanding knowledge, enhancing research, and therapeutic discovery. Issue 6 (9th March 2022) - Kontaridis, Maria I.; Roberts, Amy E.; Schill, Lisa; Schoyer, Lisa; Stronach, Beth; Andelfinger, Gregor; Aoki, Yoko; Axelrad, Marni E.; Bakker, Annette; Bennett, Anton M.; Broniscer, Alberto; Castel, Pau; et al.
Abstract: RASopathies are a group of genetic disorders that are caused by genes that affect the canonical Ras/mitogen‐activated protein kinase (MAPK) signaling pathway. Despite tremendous progress in understanding the molecular consequences of these genetic anomalies, little movement has been made in translating these findings to the clinic. This year, the seventh International RASopathies Symposium focused on expanding the research knowledge that we have gained over the years to enhance new discoveries in the field, ones that we hope can lead to effective therapeutic treatments. Indeed, for the first time, research efforts are finally being translated to the clinic, with compassionate use of Ras/MAPK pathway inhibitors for the treatment of RASopathies. This biannual meeting, organized by the RASopathies Network, brought together basic scientists, clinicians, clinician scientists, patients, advocates, and their families, as well as representatives from pharmaceutical companies and the National Institutes of Health. A history of RASopathy gene discovery, identification of new disease genes, and the latest research, both at the bench and in the clinic, were discussed.